AN EFFECT TO HANDLE THE INTER-LEAVING PSEUDO NOISE SEQUENCES - An, Bui Lai; Anh, Nguyen Thuy (Vietnam Journal of Science and Technology, 2012)
Instead of creating a inter-leaving non-linear pseudo noise (PN) sequence, we carry out a mixture component sub-sequences having 2m-1 length form to make a larger sequence of various different levels (dimensions). For the mentioned sequence, scrambler mixer generated component PN sequence is considered as a linear finite state sequence machine (LFSSM) and the algorithm for mixing bit can be considered to be an effective treatment of inter-leaving non-linear PN sequences.